Upaya Peningkatan Kemampuan Berpikir Kritis Dan Kreativitas Dalam Pembelajaran Matematika Melalui Pendekatan Open-Ended (PTK Pada Siswa Kelas XI AK-PM SMK Muhammadiyah 2 Surakarta Tahun 2016/2017) - Putri, Arum Aisa, Dra. Sri Sutarmi,M.Pd (2017)
The purpose of research this are: (1) To improve students' critical thinking skills in mathematics learning through the Open-Ended approach. (2) To improve students' creativity in mathematics learning through the Open-Ended approach. The type of the research is qualitative research with the design type action (PTK). The subjects were students of class XI AK-PM and math teacher SMK Muhammadiyah 2 Surakarta. Data collection techniques with principal method (observation and tests) as well as auxiliary method (field notes and documentation). Results: (1) There is an increased critical thinking skills of students in mathematics, including (a) the ability to provide a simple explanation by analyzing the question rose from before applying the treatment of 3 students (11.11%) after treatment to 20 students (74.07%); (b) the ability to provide further explanation by identifying the increased assumption of prior actions 2 students (7.41%) after treatment to 14 students (51.85%); (c) the ability to manage the strategy and tactics to determine and write down the solution of the problems of prior actions increased 3 students (11.11%) after treatment to 23 students (85.19); and (d) increased ability to determine the conclusion of prior actions 4 students (14.81%) after treatment to 21 students (77.78). (2) There is a growing creativity of students in mathematics, cover (a) creativity in asking to increase from before applying the treatment of 4 students (14.81%) after treatment to 18 students (66.67%); (b) creativity in expressing ideas or opinions increased from before applying the treatment of 2 students (7.41%) after treatment to 15 students (55.56%); (c) creativity in providing answers to questions of teachers increased from before applying the treatment of 2 students (7.41%) after treatment to 14 students (51.84%) and (d) creativity in doing exercises in front of the class increased from before applying the treatment of 3 students (11.11%) after the action into the 19 students (70.37%).